GE_GERICHTE P/1861/2025 vom 27. Januar 2025 - GE Cour de justice (2025)
VOL(DROIT PÉNAL);APPROPRIATION ILLÉGITIME;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DÉLAI;ESCROQUERIE | CPP.310.al1.letb; CPP.310.al1.leta; CP.139; CP.146; CP.138